Dendrodontia hyphopaxillosa (Basidiomycota, Polyporaceae), a new species with dense hyphal pegs from southern China - Li, Mengjie; Yuan, Haisheng (Phytotaxa, 2014)
Dendrodontia hyphopaxillosa, a new epithelioid species from southern China in Polyporaceae is described and illustrated. The species is characterized by resupinate, adnate, effused basidiocarps, densely distributed cylindrical hyphal pegs, frequently branched contorted dendrohyphidia and small ellipsoid to subcylindrical basidiospores. Discriminating characters between the new species and closely related species are discussed, and an identification key to the species of Dendrodontia is provided.